2012
DOI: 10.1007/s10734-012-9538-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in higher education politics: a theoretical model

Abstract: This article presents a model for analysing dynamics in higher education politics (DHEP). Theoretically the model draws on the conceptual history of political contingency, agenda-setting theories and previous research on higher education dynamics. According to the model, sociohistorical complexity can best be analysed along two dimensions: the political situation and political possibilities. Politics as a situation connotes the idea of an opportune moment when politics can be changed, and political possibiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 26 publications
(21 reference statements)
1
35
0
1
Order By: Relevance
“…Clearly, this shows that HE policy-making is now a fast growing field of study. Conducting an extensive literature search, I discovered that there were a number of studies carried out with the aim of debating some HE policy and policy-making issues (see Cook, 1998;Kauko, 2013;Lane, 2007;Marginson & Mollis, 2001;Martinez, 2002;Mills, 2007;Lowry, 2001;Richardson et al, 1999;Saarinen & Ursin, 2012). The focus of these studies has been varied and these apply the study of public policy and political science to HE.…”
Section: He Policy-makingmentioning
confidence: 99%
See 4 more Smart Citations
“…Clearly, this shows that HE policy-making is now a fast growing field of study. Conducting an extensive literature search, I discovered that there were a number of studies carried out with the aim of debating some HE policy and policy-making issues (see Cook, 1998;Kauko, 2013;Lane, 2007;Marginson & Mollis, 2001;Martinez, 2002;Mills, 2007;Lowry, 2001;Richardson et al, 1999;Saarinen & Ursin, 2012). The focus of these studies has been varied and these apply the study of public policy and political science to HE.…”
Section: He Policy-makingmentioning
confidence: 99%
“…Overall, these studies (American and European) have used several different frameworks and methods which fit with their cases and contexts. Some of the issues and themes covered in these studies are the national politics of HE (Cook, 1998), how the structure of HE systems affects HE policies (Lowry, 2001), political actors and the governance of HE (Richardson et al, 1999), policy development and state governance structures (Leslie & Novak, 2003;Martinez, 2002), the use of political frameworks in analysing policymaking in HE (Kauko, 2013;Lane, 2007;Mills, 2007), the viewpoints of policymakers, and legislators on HE policy (Bastedo, 2006), the analysis of power relations in comparison between HE systems in Australia and Argentina (Marginson & Mollis, 2001) and approaches to study HE policy (Saarinen & Ursin, 2012). These studies informed the selection of an appropriate theoretical framework for this study, as will be shown in the following chapter.…”
Section: He Policy-makingmentioning
confidence: 99%
See 3 more Smart Citations